United Kingdom : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in the United Kingdom during 1991-96. The paper examines two sets of possible reasons why the United Kingdom's savings and investment rates are lower than elsewhere. The first consists of factors leading to lower optimal rates of savings and investment: these include demographics, economic structure and technology, a liberalized financial environment, and so on. The second consists of distortions leading to lower-than-optimal savings and investment rates. The paper also presents new estimates for the potential growth rate, the output gap, and the natural rate of unemployment.